Genetic resources of cacao National type in Ecuador: a systematic review - Sornoza Vélez , Lady (2022)
In order to compile information related to Nacional type cocoa, the following review addresses i) importance of cocoa in Ecuador, ii) germplasm banks and characterization of Nacional type cocoa genotypes, iii) main production areas and iv) recommended materials for the different production areas. A systematic literature search was conducted from 1937 to 2022 in scientific databases such as Scopus, Scielo, Redalyc, Latindex.  In addition, documents were collected in repositories of national and international universities and research institutes. Descriptive and multivariate statistics were used to analyze the information. The systematic review carried out allows concluding that: i) the genetic resources of this type of cocoa are very important for the cocoa sector, ii) the main variables reported as discriminant were: number and weight of seeds and less than 50% of the accessions have been genetically characterized iii) the main producing provinces of Nacional type cocoa in Ecuador are Manabí, Guayas, Los Ríos and Esmeraldas and iv) the clones INIAP-EETP-800 and INIAP-EETP-801, with 2. 5 and 2 t/ha/year, respectively, have reported higher yields than clone CCN51. This review aims to raise awareness among the cocoa sector and consumers about the importance of maintaining this important genetic resource.